LEARN FROM SUCCESSFUL ENTREPRENEURS (Kuala Lumpur : Vanakkammalaysia Dotcom Sdn. Bhd., 2005)
There are people whom the society salutes. These people not only brought riches to their homes, but also in the process helped mankind in various ways. When you read the success stories of great individuals, there is one thing common in all of them. They are all fighters against great odds, hardships and they possessed a set of virtues like perseverance, fearlessness, creativity and an 'incanny knack to get along with different kinds of people. It was not a bed of roses for them too. They were greeted with failures on the way, disheartened at times, some were on the brink giving up, but the thing that kept them going on, was the killer instinct to succeed. They were all highly motivated people, with a commitment to excellence and an obsessive drive to win. This book would serve as a great source of inspiration and thus ignite a fire in you to achieve on similar patterns.